EXTREMA OF THE POLAR AM HER: RESULTS OF MULTITELESOOPE MONITORING - Andronov, I. L; Kimeridze, G. N.; Kolesnikov, S. V.; Pavlenko, E. P.; Bazej, N. V.; Shakhovskoy, N. M.; Smykov, V. P.; Shakun, L. I. (Одеські астрономічні публікації, 2017)
The characteristics of 250 extrema of AM Her from the photographic, photoelectric and TV observations are tabulated.